Chapter North Italian Ports and the Levant in the 16th and 17th Centuries - GHEZZI, Renato (Atti delle «Settimane di Studi» e altri Convegni, 2019)
The chapter analyzes, from a diachronic perspective, the role of trade with the Levant in the port industries of Genoa, Livorno, and Venice in the 16th and 17th centuries. An historical period in which the international trade system underwent substantial changes. From the expansion of the Atlantic routes to the official claim by the United Provinces and English, to the Italian Mariner crisis and the gradual advance of Nordic fleets along the Western Mediterranean routes. The Atlantic ships had an increasing influence on Genoa's port industry. It was, however, Livorno who gained the most advantage from the presence of Dutch and English merchant ships along routes which met at Alexandretta in San Giovanni of Acre, at Constantinople, and most of all, at Smyrna.